Building DEVS models from the functional design of software architecture components to estimate quality - Blas, María Julia; Leone, Horacio; Gonnet, Silvio (2nd. Workshop on Software-Intensive Systems Modeling and Simulation (MSSiS), 2020)
Software architectures can be used as a vehicle to improve the study of quality properties in the early stages of development. This paper proposes an automatic mapping between the design of architectural components and the specification of DEVS atomic models with aims to evaluate all-purpose quality metrics. Then, we use the functional description of architectural components (that address functional requirements) to estimate the architecture adjustment to non-functional requirements. The guidelines for structuring the simulation models are defined starting from the design of high-level components. To illustrate the proposal, web-based architecture is used as proof of concepts.
Keywords: Software architecture; Quality metrics; DEVS atomic model; Nonfunctional requirements